2020
DOI: 10.1021/acsnano.0c02237
|View full text |Cite
|
Sign up to set email alerts
|

High-Voltage Cycling Induced Thermal Vulnerability in LiCoO2 Cathode: Cation Loss and Oxygen Release Driven by Oxygen Vacancy Migration

Abstract: The release of the lattice oxygen due to the thermal degradation of layered lithium transition metal oxides is one of the major safety concerns in Li-ion batteries. The oxygen release is generally attributed to the phase transitions from the layered structure to spinel and rocksalt structures that contain less lattice oxygen. Here, a different degradation pathway in LiCoO2 is found, through oxygen vacancy facilitated cation migration and reduction. This process leaves undercoordinated oxygen that gives rise to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
115
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 186 publications
(124 citation statements)
references
References 44 publications
9
115
0
Order By: Relevance
“…[ 2,3 ] In addition, there also arises safety concerns over combustible organic electrolyte. [ 4 ] In this way, the aqueous rechargeable battery with advantages, including low cost, high operation safety, and environmental friendliness, becomes a very promising electrochemical energy storage device. [ 5 ] Moreover, the ionic conductivity in the aqueous electrolyte is higher by several orders of magnitude than that in the organic electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…[ 2,3 ] In addition, there also arises safety concerns over combustible organic electrolyte. [ 4 ] In this way, the aqueous rechargeable battery with advantages, including low cost, high operation safety, and environmental friendliness, becomes a very promising electrochemical energy storage device. [ 5 ] Moreover, the ionic conductivity in the aqueous electrolyte is higher by several orders of magnitude than that in the organic electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Sun et al used the in situ EELS and TEM imaging to evaluate the oxygen release during heating the Li x CoO 2 cathode after the high-voltage (4.6 V) cycling (Figure 9d). [90] From the EELS line scan, the O/Co ratio at the surface was lower than that in the bulk, suggesting the continuous oxygen loss near the surface region. Furthermore, they found that such thermal degradation was proceeded through the oxygen vacancies and facilitated by the cation migration and reduction.…”
Section: Thermal Stabilitymentioning
confidence: 94%
“…[1] However, a prompt increase in the energy demand because of industrialization and motorization and the associated environmental problems lead to the requisite for replacing traditional fuels with sustainable clean energy sources. [2][3][4][5][6][7][8][9][10] In this regard, the best alternatives are fuel cells and metal air batteries having zero emission and high energy conversion rate. [11][12][13][14] Among them, the oxygen reduction reaction (ORR) at cathode is of utmost importance due to the sluggish kinetics, limiting their practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Presently, about 78 % of the global energy requirement is accomplished by using fossil fuels [1] . However, a prompt increase in the energy demand because of industrialization and motorization and the associated environmental problems lead to the requisite for replacing traditional fuels with sustainable clean energy sources [2–10] . In this regard, the best alternatives are fuel cells and metal air batteries having zero emission and high energy conversion rate [11–14] .…”
Section: Introductionmentioning
confidence: 99%